The New Dawn of Critical Minerals Industry - Bhattacharya, Jayanta (Journal of Mines, Metals and Fuels, 2020)
American Geosciences Institute considers critical minerals as those that are essential to the economy and whose supply may be disrupted. Critical minerals also tend to be those on which a country is heavily import-reliant, so the minerals that are deemed critical will vary from country to country. Demand for many of these minerals has skyrocketed in recent years with the spread of high-tech devices that use a wide variety of materials.